1987
DOI: 10.1073/pnas.84.5.1324
|View full text |Cite
|
Sign up to set email alerts
|

Bizarre tRNAs inferred from DNA sequences of mitochondrial genomes of nematode worms.

Abstract: The complete nucleotide sequence of the mitochondrial DNA (mtDNA) molecule of the parasitic nematode worm Ascaris suum has been determined. This molecule lacks genes for tRNAs of the standard form. Instead, 21 sequences are found that can be folded into structures that resemble tRNAs in which the TIC arm and variable loop are missing and replaced with a single loop of between 4 and 12 nucleotides. Considerations of various properties of these sequences, including the number, predicted anticodons, conserved nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
140
0
7

Year Published

1989
1989
2009
2009

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 249 publications
(153 citation statements)
references
References 31 publications
6
140
0
7
Order By: Relevance
“…Already at the time of sequencing the first complete mitochondrial genome, that of bovine (Anderson et al 1981), it appeared that, despite a cloverleaf-like secondary structure, the mitochondrial tRNAs markedly deviate from classical tRNAs. These unexpected features have been confirmed for mitochondrial tRNAs from other organisms (e.g., Wolstenholme et al 1987) and especially from mammals. Compilation and comparison of tRNAs from 31 fully sequenced mammalian mitochondrial genomes within 22 groups (one per amino acid specificity, two for leucine, and two for serine according to the anticodon triplet) demonstrated that these tRNAs distinguish from classical tRNAs in regard of the size of D-and T-domains (especially loops) and the absence of expected conserved and semi-conserved nucleotides, leaving the understanding of three-dimensional (3D) folding of these tRNAs mainly open (Helm et al 2000), despite efforts in this direction (Steinberg et al 1997).…”
Section: Introductionsupporting
confidence: 53%
“…Already at the time of sequencing the first complete mitochondrial genome, that of bovine (Anderson et al 1981), it appeared that, despite a cloverleaf-like secondary structure, the mitochondrial tRNAs markedly deviate from classical tRNAs. These unexpected features have been confirmed for mitochondrial tRNAs from other organisms (e.g., Wolstenholme et al 1987) and especially from mammals. Compilation and comparison of tRNAs from 31 fully sequenced mammalian mitochondrial genomes within 22 groups (one per amino acid specificity, two for leucine, and two for serine according to the anticodon triplet) demonstrated that these tRNAs distinguish from classical tRNAs in regard of the size of D-and T-domains (especially loops) and the absence of expected conserved and semi-conserved nucleotides, leaving the understanding of three-dimensional (3D) folding of these tRNAs mainly open (Helm et al 2000), despite efforts in this direction (Steinberg et al 1997).…”
Section: Introductionsupporting
confidence: 53%
“…As in other mammals, 22 tRNA genes were found in the dog mtDNA, and had a similar organization. The small number of tRNA genes in the mammalian mtDNA is thought to be the result of strong pressure for the economization of the genome size (Anderson et al, 1981(Anderson et al, , 1982Bibb et al, 1981;Clary and Wolstenholme, 1985;Wolstenholme et al, 1987;Gadaleta et al, 1989;Desjardins and Morais, 1990;Okimoto et al, 1992). The structural features of the dog mitochondrial tRNA molecules, such as the anticodon (AC) stem and loops, T-⌿-C, and amino acid-acceptor (A-A) arms, showed an L-shaped tertiary structure identical to those found in other mammalian mitochondrial tRNA molecules (Cedegren et al, 1981;Kumazawa and Nishida, 1993).…”
Section: Trna and Rrna Genesmentioning
confidence: 99%
“…The nematode mtDNA genetic code (Wolstenholme et al, 1987;Okimoto et al, 1992) was used to predict amino acid sequences from the 582 nt obtained for all taxa. Predicted polypeptide sequences were aligned using CLUSTAL V (Higgins et al, 1992); alignment of the coding nucleotide sequences was straightforward.…”
Section: Sequence Analysismentioning
confidence: 99%